Learning microbiology through clinical consultation - Langdon, Berenice C.; Breathnach, Aodhán S. (Oxford University Press, 2016)
'Learning Microbiology through Clinical Consultation' is a highly accessible text which describes the fundamentals of microbiology within the practice setting in an informative way. It is an ideal resource for medical students and newly qualified doctors, as well as anyone wishing to study medicine or preparing for medical school interviews.